2021
DOI: 10.1111/cts.12984
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of the serum from children with urolithiasis using UPLC‐MS

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…These results indicated that the metabolic phenotype of serum in patients with kidney stones was significantly different from that found in normal controls. The study provided a new understanding into the potential pathogenesis of urolithiasis, which may help to develop novel therapeutic strategies and preventive interventions [53]. Metabolomics can also be used to identify and quantify metabolites from plants.…”
Section: Application Of Uhplc In Pharmacokinetics and Bioavailability...mentioning
confidence: 99%
“…These results indicated that the metabolic phenotype of serum in patients with kidney stones was significantly different from that found in normal controls. The study provided a new understanding into the potential pathogenesis of urolithiasis, which may help to develop novel therapeutic strategies and preventive interventions [53]. Metabolomics can also be used to identify and quantify metabolites from plants.…”
Section: Application Of Uhplc In Pharmacokinetics and Bioavailability...mentioning
confidence: 99%
“…Wen et al [33] reported serum metabolomics assayed with LC-MS in 30 SF (10 CaOx, 10 cysteine, 10 calcium carbonate, mean age 5 AE 4) compared with 20 non-SF of similar age. Metabolites differed between SF and non-SF, and also between the three SF groups.…”
Section: Linking the Microbiome And Metabolome In Stone Formersmentioning
confidence: 99%
“…In the recent years, advances in the knowledge of the role of metabolism in the development and progression of this condition have been reported [ 87 ]. In particular, branches of omics such as metabolomics have investigated the change in metabolites linked to lithiasis [ 88 ].…”
Section: Metabolomics In Kidney Stone Diseasementioning
confidence: 99%
“…Wen et al [ 88 ] analyzed the change in metabolites in patients with urolithiasis through serum metabolomics based on ultra-performance liquid chromatography mass spectrometry. The authors investigated a total of 50 patients (30 children with kidney stones and 20 controls) enrolled between January 2018 and July 2019.…”
Section: Metabolomics In Kidney Stone Diseasementioning
confidence: 99%
See 1 more Smart Citation